2018
DOI: 10.32861/ijefr.5.410.303.312
|View full text |Cite
|
Sign up to set email alerts
|

Oil and Gas Production and the Growth of Ghana’s Economy: An Initial Assessment

Abstract: Oil and gas resources present enormous opportunities for the economic development of low income economies, but poor management of these resources can result in dire consequences for the foundations of the resource-endowed nation. The discovery of oil and gas in Ghana is as significant as the policies and measures to ensure optimum benefits to the nation. This paper evaluates the sustainability of petroleum production in the light of the medium term policy structure, the Ghana Shared Growth and Development Agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…The magnitude and the sign of the coefficient of oil resource rent imply that 1% increase in oil revenue generates 0.84% increase in GDP, ceteris paribus. This finding is consistent with some existing studies (Olayungbo, 2019;Lukman et al, 2018;Ahmad and Masan, 2015) but contradicts findings from Wang et al (2021) and Acquah-Andoh et al (2018). Economically, this implies that the extraction of crude oil generates revenue to both the producing firm and government, which is shared between the two parties based on law/contract.…”
Section: Co-integration Test Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The magnitude and the sign of the coefficient of oil resource rent imply that 1% increase in oil revenue generates 0.84% increase in GDP, ceteris paribus. This finding is consistent with some existing studies (Olayungbo, 2019;Lukman et al, 2018;Ahmad and Masan, 2015) but contradicts findings from Wang et al (2021) and Acquah-Andoh et al (2018). Economically, this implies that the extraction of crude oil generates revenue to both the producing firm and government, which is shared between the two parties based on law/contract.…”
Section: Co-integration Test Resultssupporting
confidence: 85%
“…We now focus on some studies within Sub-Sahara Africa and its environment that used different estimation strategies to examine the relation between oil production and economic growth. Within this literature, Acquah-Andoh et al (2018) examine linear relationship between oil production and Ghana's GDP growth using ordinary least squares (OLS) regression as an estimation strategy. They found that recent production of oil does not contribute significantly to the GDP growth of Ghana.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturing sector alone in Ghana accounts for about 25.3% of the total gross domestic product. Ghana's industrial production is rising at a 7.8% rate, giving it the 38th fastest growing industrial production in the world because of government industrialization policies (Mekpor and Dartey-Baah, 2019;Acquah-Andoh et al, 2018). Although these trends in the sector look promising, it is becoming increasingly difficult to attract and retain employees who are fully engaged with Responsible leadership and duty orientation 921 their work.…”
Section: Introductionmentioning
confidence: 99%
“…The policy was also to encourage the development and use of renewable energy resources and create a climate conducive to investment in renewable energy resources. The policy was as well to promote the use of renewable energy, diversify renewable energy supplies to provide energy security and enhance access to electricity [23,[47][48][49][50] . Public education on renewable energy production and use is needed to establish indigenous capacity in renewable energy technology in order to fulfil the goals of other international bodies [21] .…”
Section: The Purposes Of Ghanaian Government Renewable Energy Lawmentioning
confidence: 99%